Justice Cruz Reynoso Fundraiser at William Saroyan Theatre Lower Lobby - Watkins, Howard::::::::: (1986)
Judge Armando Rodriguez, Justice Cruz Reynoso, Leo Valdivia and Carlos Cabrera; seated to right Father Arturo Gomez and Jorge Acuna